PENGARUH MOTIVASI BELAJAR DAN KESIAPAN BELAJAR SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN KEWIRAUSAHAAN MELALUI PEMBELAJARAN BERBASIS CASE METHOD DI SMKS SYEKH MUHAMMAD JA’FAR - Septiana Anugrah. S; Mustafa; Syamsu A Kamaruddin (STKIP Subang, 2025)
This study aims to analyze the influence of learning motivation and students’ learning readiness on the learning outcomes of the Entrepreneurship subject by incorporating case-method–based learning as an intervening variable among tenth-grade students at SMKS Syekh Muhammad Ja’far. The phenomenon observed in the school shows variations in students’ learning outcomes, which are presumed to be influenced by low learning motivation and insufficient learning readiness in facing the learning process. The case method approach is expected to enhance students’ understanding through the analysis of real-life cases, collaborative discussions, and the development of critical thinking skills in solving problems. This research employs a quantitative method with an ex post facto design and a causal associative approach. The instrument used was a Likert-scale questionnaire administered to tenth-grade students, and the data were analyzed using validity and reliability tests, multiple linear regression, classical assumption tests, and path analysis. The results indicate that both learning motivation and learning readiness have a positive and significant effect on learning outcomes. In addition, these variables also significantly influence case-method–based learning, which in turn positively impacts learning outcomes. Path analysis shows that the case method serves as an effective mediator in strengthening the relationship between learning motivation and learning readiness with students’ learning outcomes. Overall, case-method–based learning plays a crucial role in optimizing learning activities and improving the quality of student learning outcomes in the Entrepreneurship subject. These findings provide practical implications for teachers in designing more innovative and student-centered learning strategies. Keyword: learning motivation, learning readiness, case method, entrepreneurial learning, learning outcomes.